Understanding the Societal Impact of the Social Sciences and Humanities: Remarks on Roles, Challenges, and Expectations - Fecher, Benedikt; Kuper, Freia; Sokolovska, Nataliia; Fenton, Alex; Hornbostel, Stefan; Wagner, Gert G. (Frontiers in Research Metrics and Analytics, 2021)
Science is increasingly expected to help solving complex societal problems in collaboration with societal stakeholders. However, it is often unclear under what conditions this can happen, i.e. what kind of challenges occur when interacting with society and what kind of quality expectations prevail. This is particularly pertinent for SSH, who are part of the object they study and whose knowledge is always subject to provisionality. Here we discuss how SSH researchers can contribute to societal problems, what challenges might occur when they interact with societal stakeholders, and what quality expectations arise in these arrangements. We base our argumentation on the results of an online consultation among 125 experts in Germany (i.e., representatives from SSH, learned societies, stakeholder from different societal groups, and relevant intermediaries). Based on our results, we propose a quality framework for productive interactions involving the SSH.